Pengaruh Keadilan Organisasional pada Komitmen Organsasional dengan Kepuasan Kerja sebagai Variabel Intervening (Management Analysis Journal, 2015)
The purpose of this study was to investigate the influence of job satisfaction variables as a mediating role between organizational justice to organizational commitment. The population in this study were employee’s PT. Purinusa Ekapersada with incidental sampling data collection techniques and the sample were 199 people using incidental sampling.The methods used in collecting the data was a questionnaire which was measured by likert scale. Analysis was partia test and The sobel analysis used SPSS 20 . The results showed that there was significant positive effect between organizational justcice on the job satisfaction. Significant and positive effect also showed between job satisfaction on the organizational commitment. While organizational justice showed not significant effect on the organizational commitment. Job satisfaction shown to have influence as a mediate role the relationship organizational justice on organizational commitment. The conclusion from this research that job satisfaction plays an important role in the onset of organizational commitment. Organizational justice does significantly affect on job satisfaction, but does not significantly affect on the organizational commitment, which means that organizational commitment be affected more seriously by other important factors, such as employess satisfaction and high salary.